2005
DOI: 10.1167/iovs.05-0187
|View full text |Cite
|
Sign up to set email alerts
|

Antigen/MHC Class II/Ig Dimers for Study of Uveitogenic T Cells: IRBP p161–180 Presented by both IA and IE Molecules

Abstract: Uveitogenic T cells can be detected as well as functionally modulated with their cognate peptide-class II reagent, suggesting the potential of such reagents for diagnostic and therapeutic use in uveitic disease; p161-180 can be presented by IA(r) as well as IE(r) major histocompatibility complex (MHC) class II molecules. The possibility that the same immunodominant fragment might be presented by more than one class II molecule should be taken into account when diagnostic or clinical use of peptide-MHC reagents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Initially, CD4 + autoreactive T cells were believed to be the major pathogenic T cells in autoimmune diseases, such as experimental autoimmune encephalitis (EAE) and EAU (Gregerson et al, 1986,Jones et al, 1997,Karabekian et al, 2005). This conclusion was chiefly supported by the observations that cultured autoreactive T cells in such diseases (Sun et al, 1988) (Tuohy et al, 1988,Reddy et al, 2003; (Rizzo et al, 1996,Rozenszajn et al, 1986,Gregerson et al, 1986 are exclusively CD4 + αβTCR + and that, upon transfer to syngeneic naive animals, these CD4 + autoreactive T cell lines are capable of causing the related autoimmune disease (Gregerson et al, 1986,Rizzo et al, 1996,Rozenszajn et al, 1986.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, CD4 + autoreactive T cells were believed to be the major pathogenic T cells in autoimmune diseases, such as experimental autoimmune encephalitis (EAE) and EAU (Gregerson et al, 1986,Jones et al, 1997,Karabekian et al, 2005). This conclusion was chiefly supported by the observations that cultured autoreactive T cells in such diseases (Sun et al, 1988) (Tuohy et al, 1988,Reddy et al, 2003; (Rizzo et al, 1996,Rozenszajn et al, 1986,Gregerson et al, 1986 are exclusively CD4 + αβTCR + and that, upon transfer to syngeneic naive animals, these CD4 + autoreactive T cell lines are capable of causing the related autoimmune disease (Gregerson et al, 1986,Rizzo et al, 1996,Rozenszajn et al, 1986.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently demonstrated that, in both the Lewis rat (Shao et al, 2004) and B6 mouse (Shao et al, 2005a); (Peng et al, 2007), many CD8 autoreactive T cells are activated and actively participate in disease pathogenesis. To determine whether this observation applies to other EAU models, we tested the B10RIII mouse, which is the mouse strain most susceptible to EAU (Hankey et al, 2001,Karabekian et al, 2005. Since our previous studies demonstrated that CD4 and CD8 IRBP-specific T cells in the B6 mouse both responded to the same antigenic epitope (Shao et al, 2005a), we were also interested in testing whether this was also true in the B10RIII mouse.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been implicated in antigen specific induction of anergy to CD4 + T cells which play crucial roles in a number of autoimmune diseases and therefore it has been possible to apply these types of dimers in studies to combat autoimmune diseases among them type 1 diabetes and multiple sclerosis [53][54][55][56]. Karabekian et al showed that an engineered 161-180/IA r /Ig dimer, produced in insect cells, binds to a uveitogenic 161-180-peptide specific T-cell line and lead to antigen specific T cell proliferation or anergy depending on the presence or absence of co-stimulation [57]. Although most studies using MHC-Ig dimers of class II in origin have looked at autoimmune disease, these studies have also suggested that these dimers may have a role to play in transplantation immunology as well.…”
Section: Mhc Class II -Ig Dimersmentioning
confidence: 99%
“…In addition to MHC tetramer technology based on the biotin-streptavidin system, staining with dimeric reagents carrying two MHC/peptide complexes on an IgG scaffold is an alternative method to detect antigen-specific T cells (Greten et al 1998;Karabekian et al 2005). In this study, HLA/peptide complex containing a His-tag was mixed with the anti-His-tag mAb, and then PE-labeled rat anti-mouse a 5.2 mg HC protein was added into 50 ml refolding buffer b 3 mg HC protein was applied to a 5 ml Q-Sepharose HP column, and 2.5 mg protein was on the column c 2 mg HC protein was applied to a 5 ml Q-Sepharose HP column, and 1.8 mg protein was on the column d Refolding yield is analyzed by the HC protein before the refolding process and after purification (Garboczi et al 1992) IgG mAb is used to label anti-His-tag mAbs for the formation of multimerized HLA/peptide complex.…”
Section: Detection Of Hbc 18-27 -Specific T Cellsmentioning
confidence: 99%